2014
DOI: 10.1016/j.ihj.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and outcomes of transcatheter closure of complex atrial septal defects – Single center experience

Abstract: Trans catheter closure is feasible in anatomically complex substrates of Secundum ASD. Careful case selection, scrupulous imaging protocol, and expertise in modified techniques are mandatory for successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…The presence of multiple defects of the inter-atrial septum have been reported between 5.3% to 7.3% of patients with ostium secundum ASD. 2,6,7 In our study Aortic rim was absent in 63.3 % patients, it is the rim which is most commonly absent in ASD secundum patients. Though absent Aortic rim is not a contraindication for device closure, its absence makes device closure procedure complex.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The presence of multiple defects of the inter-atrial septum have been reported between 5.3% to 7.3% of patients with ostium secundum ASD. 2,6,7 In our study Aortic rim was absent in 63.3 % patients, it is the rim which is most commonly absent in ASD secundum patients. Though absent Aortic rim is not a contraindication for device closure, its absence makes device closure procedure complex.…”
Section: Discussionsupporting
confidence: 48%
“…Deficient/floppy posterior rim was present in 30.6% patients. 6 IVC rim is the most important rim for ASD device closure, absence of IVC rim is considered contraindication for Device therapy. IVC rim was absent in 20% patients and floppy in 47% patients.…”
Section: Discussionmentioning
confidence: 99%
“…Deficient aortic rim is a rather common morphologic feature of ASD and is present in up to 30-50% of ASDs that are considered complex [16]. Deficient aortic rim is a risk factor for aortic erosion after device closure of ASDs.…”
Section: Deficient Aortic Rimmentioning
confidence: 99%
“…The defect morphology determines the indication for transcatheter treatment. In cases of multiple defects, percutaneous device closure is not generally indicated [3] , [4] . We report a case in which a single ostium secundum type ASD masqueraded as multiple defects on color flow imaging due to a refraction artifact.…”
Section: Introductionmentioning
confidence: 99%